BARRIERS AND FACILITATORS IN DIGITAL HEALTH FOR ANTENATAL CARE: A SCOPING REVIEW - Fitri Kurnia Rahayu; Nunik Puspitasari; Nurul Fitriyah; Evita Kumala Dewi; Andi Safutra Suraya; Yulia Yunara (Indonesian Journal of Health Administration (Jurnal Administrasi Kesehatan Indonesia), 2026)
Background: Digital health technologies have great potential to improve antenatal care quality and accessibility. However, their implementation is hindered by various barriers and supported by certain facilitators, influenced by both health workers' and patients' perspectives. Aim: To identify and map these barriers and facilitators in the implementation of digital health technologies in antenatal care, focusing on insights from both health providers and patients. Method: This scoping review systematically searched and analyzed literature, including studies published from 2014 to 2024 on the implementation of digital health solutions in antenatal care services. Sources included PubMed, Scopus, Web of Science, and CINAHL. Results: 484 studies were screened, 38 were assessed in full text, and 16 were included. These studies covered various digital technologies such as PANDA System, eHealth Technologies, SMS-based solutions, Telemonitoring, and mobile applications. Key barriers for providers include lack of readiness and technical issues, while facilitators include care standardization and health worker support. Patients face barriers such as technological illiteracy and financial constraints, while high user satisfaction and culturally adapted approaches are facilitators. Conclusion: Addressing both provider readiness and patient needs is crucial for effective implementation of digital health technologies in antenatal care, requiring a comprehensive approach to overcome barriers and enhance facilitators. Keywords: antenatal care, barriers, digital health, facilitators, health workers, patients, scoping review